Analisis Persepsi Anggota Jemaat Tentang Karakter Kepemimpinan Pekaindoran dan Implikasinya Bagi Majelis Gereja Toraja Jemaat Malolo Sesesalu Klasis Rembon Sadoko’ - Melianti Paonganan (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: Where in the Malolo Sesesalu, members of the congregation usually experience cases of disputes, but from the cases that occur the congregation members tend to report to pesindoran as a customary goverment rather than to the church assembly. It means that the members of the congregation are more trusting in the pekaindoran to solve problems than the church council.The purpose of this research is to describe the perceptions of congregation members about the leadership character of pekaindoran and the implication for the Toraja church assembly of the Malolo Sesesalu as a classic Rembon Sado’ko’. The method that the author intends to use in completing this paper is a qualitative research method whose data were obtained through interviews, observations, and literature studies.The results of the research obtained from the field, the congregation members have the view that the leadership character of Pekaindoran has good character values such as fair, firm and even the members of the congregation really feel the leadership of Pekaindoran. Keywords: Character, Leadership, Pekaindoran Abstrak: Di jemaat Malolo Sesesalu warga jemaat biasa mengalami kasus perselisihan namun dari kasus yang terjadi warga jemaat cenderung melapor ke Pekaindoran sebagai pemerintahan adat dibandingkan ke majelis gereja. Artinya bahwa warga jemaat lebih percaya kepada Pekaindoran untuk menyelesaikan masalah dari pada majelis gereja.Tujuan penelitian ini untuk mendeskripsikan persepsi anggota jemaat tentang karakter kepemimpinan Pekaindoran dan implikasinya bagi majelis gereja toraja jemaat Malolo Sesesalu klasis rembon sado’ko’. Metode yang hendak dipakai penulis dalam merampungkan karya tulis ini adalah metode penelitian kualitatif yang perolehan datanya melalui wawancara, observasi dan studi pustaka.Hasil penelitian yang diperoleh dari lapangan, warga jemaat memiliki pandangan bahwa karakter kepemimpinan Pekaindoran memiliki nilai-nilai karakter yang baik seperti adil, tegas dan bahkan warga jemaat sangat merasakan kepemimpinan dari Pekaindoran. Kata kunci: Karakter, Kepemimpinan, Pekaindoran